Pengaruh Marketing B2B (Business to Business) Terhadap Penjualan Meeting Room di Sekuro Village Beach Resort Jepara - Intan Alifia; Andhi Supriyadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to determine how much influence the B2B (Business to Business) marketing variable has on meeting room sales at Sekuro Village Resort. This study uses a quantitative approach with a survey method involving 39 respondents from various companies or organizations that have used meeting room services at Sekuro Village Beach Resort. Data were collected through questionnaires and analyzed using simple linear regression analysis with the help of IBM SPSS software version 25. The results of the study indicate that there is a positive and significant influence between the B2B marketing strategy implemented and the increase in meeting room sales at Sekuro Village Beach Resort. The conclusion of this study is that the implementation of an effective B2B marketing strategy can substantially increase meeting room sales at Sekuro Village Beach Resort. The implication of this study is the importance of Sekuro Village Beach Resort to continue to develop a B2B marketing strategy that focuses on the needs and satisfaction of corporate clients to increase competitiveness and sales.